First- and Second-Trimester Reference Intervals for Thyroid Hormones during Pregnancy in "Rhea" Mother-Child Cohort, Crete, Greece. (4th December 2011) - Karakosta, Polyxeni; Chatzi, Leda; Bagkeris, Emmanouil; Daraki, Vasiliki; Alegakis, Dimitris; Castanas, Elias; Kogevinas, Manolis; Kampa, Marilena
Abstract : Estimation and interpretation of thyroid function tests in pregnant women is of utmost importance for maternal, fetal and neonatal health. Our objective was to calculate laboratory- and geography-specific reference intervals for thyroid hormones during pregnancy in an iodine-sufficient area of the Mediterranean, Crete, Greece. This project was performed in the context of "Rhea" mother-child cohort. Fulfillment of extensive questionnaires and estimation of free triiodothyronine (fT3), free thyroxine (fT4), thyroid-stimulating hormone (TSH), and antithyroid antibodies were performed. The reference population was defined using inclusion criteria regarding thyroidal, obstetric, and general medical status of women. Reference interval for TSH was 0.05–2.53  μ IU/mL for the first and 0.18–2.73  μ IU/mL for the second trimester. 6, 8% and 5, 9% of women in the first and second trimester, respectively, had TSH higher than the upper reference limit. These trimester-specific population-based reference ranges are essential in everyday clinical practice for the correct interpretation of thyroid hormone values and accurate classification of thyroid disorders.